Domain wall dynamics in nanocrystalline microwires. Issue 5 (8th April 2014) - Klein, Peter; Varga, Rastislav; Vazquez, Manuel
Abstract: The domain wall velocity in amorphous microwires approaches very high values up to 20 km/s but dynamics is extremely sensitive to time and temperature. On the other hand, high stability in crystalline materials is paid by very low velocity of the domain wall. One possible solution is using of nanocrystalline material, which are produced by controlled annealing from amorphous precursors. Domain wall velocity reaches up to 1 km/s in nanocrystalline microwires based on FINEMET composition. In different group of nanocrystalline microwires based on HITPERM composition was observed temperature stable and fast domain wall up to 3 km/s. In the present contribution, we present new class of nanocrystalline microwires based on FeNiMoB composition, where domain wall velocity up to 12 km/s was observed. In generally, domain wall velocity increases by annealing in FeNiMoB microwires in contrary to FeCoMoB microwires. (© 2014 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)